Caracterización fisicoquímica, nutricional y sensorial de dos complementos alimenticios biofortificados. - Molina Castillo, María Carolina; Varela García, Nathalia; Jaramillo Yepes, Faiber; Valencia Naranjo, Alejandra; Gómez Velásquez, Santiago; Agudelo Martínez, María Alejandra (Archivos Latinoamericanos de Nutrición)
Introduction: Nutrition and food sciences innovate in the industry by elaborating products with nutritional compounds that contribute to the resolution of public health problems. But, in addition to nutritional characteristics, sensory characteristics are important, being a determining factor in the acceptance of these products. Objective: To evaluate physicochemical, nutritional and sensory characteristics of two food supplements, soup and chocolate drink, developed with biofortification. Materials and methods: Three phases were considered: phase 1, preparation of two types of food supplements (4 formulations), using freeze-drying for dehydration of some raw materials, complemented with other processing and cooking techniques. Phase 2, sensory evaluation by expert panel through quantitative descriptive and hedonic test, and phase 3, bromatological characterization. The analysis of the information was carried out with Jamovi 2.3.21. software through descriptive and inferential analysis. Results: The sensory analysis showed that foods containing 5% beef heart were the most accepted by the panelists in all sensory attributes in both supplements. The bromatological characterization showed that the chocolate drink type supplement with heart is an excellent source of protein, zinc and calcium and a good source of iron and vitamin E, while the soup type supplement with heart is an excellent source of protein, zinc, iron, thiamine, omega 3, vitamin E and a good source of calcium in accordance with Colombian regulations on nutritional labeling and labeling. Conclusions: Both supplements with heart showed a satisfactory sensory acceptance, presented an important concentration of nutrients, which, due to their natural and animal source, are considered of high bioavailability.